The political economy of Mexico - Glade, William P.; Anderson, Charles W. (Madison : University of Wisconsin Press, 1963)
The Political Economy of Mexico includes two separate studies. Revolution and Economic Development by William P. Glade and Bankers as Revolutionaries. By Charles W. Anderson a political scientist. Glade's thesis is that revolution almost always precedes structural reform. In Mexico the Revolution of 1910, which swept away the Porfirian facade, was the catalyst for it. Politics and Development Banking' indicates, is a case study of politically controlled credit institutions in a Mexico in the process of change.
Includes index.
Includes bibliographical references: p. 192-196.
lje 08/10/2018
Loans
Keywords: Development banks; Banks and banking; Mexico